Intensive Strategy for Growing Competitiveness of Classico Jersey - Tjutjusaputra, Aswin Agustinus; Rudito, Bambang (The Indonesian Journal of Business Administration, 2015)
Abstract.Â Classico is a company that offer clothing manufacture service. Classico established in Bandung in 2013. Classico need to create competitiveness in order to survive in clothing business. But in the first year operation of Classico, the owner faced several problems that need to be addressed. The problems are low brand awareness in consumer perspective, low quality and lack of human resources that affect the performance. To address the problems, external and internal analysis need to be conducted. The factors will be described in SWOT analysis that shows the strengths, weaknesses, opportunities, and threats for Classico, and then it will be defined in EFAS (External Factor Analysis Summary), IFAS (Internal Factor Analysis Summary), and SFAS (Strategic Factor Analysis Summary).The results of EFAS & IFAS will be defined further in IE Matrix to show the position of Classico which is in IV quadrant (develop and expand). After that, to determine which is the most attractive strategy between intensive or integrative, Quantitative Strategic Planning Matrix (QSPM) analysis need to be done and also there will be new suggestions on segmentation, targetting, and positioning. In the last chapter, based on the business issue, there will be some conclusions and suggested alternative solutions for the implementation plan that will be implemented on Classico. The most attractive strategy is intensive strategy consisting of market penetration, market development, and product development.Keywords: Clothing Manufacture, Business Strategy, Intensive StrategyÂ